(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2025)
Background: Management of primary intracerebral haemorrhage is very important in the context of outcomes. Objective: The purpose of the present study was to compare the outcomes of surgical and non-surgical management of primary intracerebral haemorrhage. Methodology: This non-randomized clinical trial study was conducted in the Department of Neurosurgery at Dhaka Medical College Hospital, Dhaka, Bangladesh from January 2006 to December 2007 for a period of two (02) years. All patients with primary intracerebral haematoma admitted in the Department of Neurosurgery in study period managed conservatively or surgically is the study population. Selected patients were divided into two group of which patients in group A were treated surgically and the group B patients were treated conservatively. Best medical treatment was given for nonsurgical group and operation were done for surgical group and followed up after surgery till discharge by observing GCS, neurological improvement and GOS at discharge. Results: Of the total 60 subjects selected for study, 30 cases were in group A and the rest of 30 cases were in group B. The both groups were almost identical in terms of age. Distribution of patients in relation to age had no significant difference (P=0.7). In group A 13(43.3%) patients were died and the survival rate was in 17(56.6%) cases. On the other hand, in group B mortality rate were 15(50.0%) patients and survival rate were 15(50%) patients (P=0.605). Considering the Glasgow outcome scale, in group A 13(43.3%) patients died and 7(23.3%) patients had severe and moderate disability and 3(10.0%) patients had good outcome. In group B 15(50%) patients died and 8(26.7%) patients had severe disability as well as 7(23.3%) patients had moderate disability (p=0.360). Conclusion: In conclusion there is no significant difference of outcomes of surgical and non-surgical management of primary intracerebral haemorrhage. Journal of National Institute of Neurosciences Bangladesh, January 2024;10(1):12-16